2023
DOI: 10.1111/jace.19271
|View full text |Cite
|
Sign up to set email alerts
|

Realization of diversity in physical properties of Zr2Se(B1‐xSex) MAX phases through DFT approach

Abstract: The discovery of a series of MAX phases, Zr2Se(B1‐xSex), with Se at both A‐ and X‐sites, drives a new chemical diversity to the MAX family. Here, we employed the density functional theory (DFT) approach to realize the diversity in physical properties of Zr2Se(B1‐xSex). All compositions of Zr2Se(B1‐xSex) are mechanically stable and the dynamical stability of the end member Zr2SeSe is confirmed. The elastic constant C33 and bulk moduli B show a decrease almost monotonically with Se‐content x while other constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 96 publications
1
5
0
Order By: Relevance
“…In a previous study, we observed that the Gou model provides hardness values similar to the experimental results if the M–A bond is excluded . Moreover, in a recent paper, we found a good matching of hardness from E with the experimental value . If the Hf–S bond is not taken into account, the Gou model gives a hardness value of 3.18 GPa for Hf 2 SB.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…In a previous study, we observed that the Gou model provides hardness values similar to the experimental results if the M–A bond is excluded . Moreover, in a recent paper, we found a good matching of hardness from E with the experimental value . If the Hf–S bond is not taken into account, the Gou model gives a hardness value of 3.18 GPa for Hf 2 SB.…”
Section: Resultssupporting
confidence: 72%
“…For evaluating θ D of partially ceramic crystals such as the MAX phase, the Anderson method has been found to be best suited and which formulate its mathematical expression as θ D = ( h / k B )­(3 n ρ N A /4π M ) 1/3 v m , in which h , k B , n , ρ, π, N A , and M are the most familiar symbols in Physics and Chemistry and v m is the average sound velocity that can be calculated from the transverse and longitudinal velocities v t and v l by v m = [1/3­(1/ v l 3 + 2/ v t 3 )] −1/3 . The transverse and longitudinal velocities v t and v l can be calculated from the bulk modulus B , shear modulus G , and mass density ρ by v l = [(3 B + 4 G )/3ρ] 1/2 and v t = [ G /ρ] 1/2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A family of layered transition-metal carbides or/and nitrides, called MAX phases (short for M n +1 AX n and usually, n = 1, 2, or 3), where M is an early transition metal, A is often from groups 13–16, and X is C and/or N, have raised much attention due to their intrinsically integrated metallic and ceramic properties, which endows them with potentials for multidisciplinary applications. In addition, recently, there have been many studies on MAB, , a layered material similar to MAX phases. Moreover, the A-site atoms usually possess superior capacities for lithium storage, and the robust MAX matrix could enable a satisfactory cyclic life. However, the conventional synthesis strategies often result in large particles, which leads to underutilization of active sites and poor electrical contact between particles, ultimately limiting its comprehensive electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%